2015
DOI: 10.3906/sag-1405-20
|View full text |Cite
|
Sign up to set email alerts
|

Fetal health locus of control in a sample of pregnant Turkish women

Abstract: Background/aim: To examine the relationship between sociodemographic and pregnancy features and fetal health locus of control (FHLC) in a sample of pregnant Turkish women. Materials and methods:The study was conducted with 256 pregnant women. Data were collected by demographic questionnaire and the FHLC Scale consisting of 3 components: 1) Internality Scale (FHLC-I), 2) Powerful Others Scale (FHLC-P), and 3) Chances Scale (FHLC-C).Results: The age of marriage was found to have a positive relation with FHLC-I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…In addition to sociodemographic factors, the culture in which the pregnant woman lived affected her prenatal attachment in terms of the meaning attributed to pregnancy and babies (Erdemoglu & Derya, 2018;Pattanasombutsook et al, 2020). One of the factors that affect the health of the mother and that of the baby is the expectant mother's health-related beliefs and attitudes (Ozcan & Duyan, 2015;Turriff-Jonasson, 2004). Upon the comparison of the mean FHLC subscale scores of the participants according to their sociodemographic and obstetric characteristics, this study found that there were statistically significant differences in the mean FHLC subscale scores of the participants based on their education levels, whereas there was no statistically significant difference based on their age, status of having a planned pregnancy, gestational week or risk status of their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sociodemographic factors, the culture in which the pregnant woman lived affected her prenatal attachment in terms of the meaning attributed to pregnancy and babies (Erdemoglu & Derya, 2018;Pattanasombutsook et al, 2020). One of the factors that affect the health of the mother and that of the baby is the expectant mother's health-related beliefs and attitudes (Ozcan & Duyan, 2015;Turriff-Jonasson, 2004). Upon the comparison of the mean FHLC subscale scores of the participants according to their sociodemographic and obstetric characteristics, this study found that there were statistically significant differences in the mean FHLC subscale scores of the participants based on their education levels, whereas there was no statistically significant difference based on their age, status of having a planned pregnancy, gestational week or risk status of their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Since culture affects health beliefs and attitudes, another reason for inconsistency of the present study with the two can be explained through cultural differences in different populations. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…FHLC has two dimensions; in this case, internal dimension suggests that the mother believes she has control on the fetal health, and if she believes that chance or other powerful individuals have control over it, she has external dimension. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Neymotin and Nemzer has also detailed a concept around “locus of control” as relates to obesity [ 16 ]. Health locus of control has been associated with a variety of health outcomes and designed to predict behaviors and cognitive processes relevant to both mental and physical health [ 17 , 18 ]. In the context of energy balance, this concept suggests that, in humans, overlaid on the complex system for modulating energy intake, there exists a wide variation in “perceived locus of control”.…”
Section: Developmental Programming and Disorders Of Energy Balancementioning
confidence: 99%